2019
DOI: 10.1177/1076029619828113
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases and Their Inhibitors and Proteoglycan 4 in Patients Undergoing Total Joint Arthroplasty

Abstract: Osteoarthritis, a degenerative disease of the joints, is the most common form of arthritis in the knee. Total joint arthoplasty is a commonly used treatment for joint degeneration and osteoarthritis, and due to these factors, TJA for hip and knee joints is projected to grow by 137% and 601% between 2005 and 2030. Matrix metalloproteases are enzymes found in the extracellular matrix that cleave matrix components. Normally MMPs are downregulated in tissues by Tissue Inhibitors of Metalloproteases, or TIMPs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…They found that TIMP‐1 was associated with clinical symptoms and radiographic features of OA. Similarly, Thorson et al, 17 found increased level of TIMP‐1 in people with OA than normal people although not statistically significant. These results suggest that macrophage and neutrophil activation lead to elevated TIMP‐1 and MMP‐3 with subsequent cartilage destruction.…”
Section: Discussionmentioning
confidence: 86%
“…They found that TIMP‐1 was associated with clinical symptoms and radiographic features of OA. Similarly, Thorson et al, 17 found increased level of TIMP‐1 in people with OA than normal people although not statistically significant. These results suggest that macrophage and neutrophil activation lead to elevated TIMP‐1 and MMP‐3 with subsequent cartilage destruction.…”
Section: Discussionmentioning
confidence: 86%
“…3D). Plasma concentrations of PRG4 measured by ELISA were as low as *100 ng/mL (*1 order of magnitude lower than the reported normal plasma concentration of PRG4), 51 and this value is an overestimation of the actual levels of intact PRG4 given that the ELISA used could not distinguish an intact PRG4 from its degradation products.…”
Section: Discussionmentioning
confidence: 68%
“…Using the in vitro model of the BBB, we showed that PRG4 can enter the brain through a high-capacity, saturable transport system. Our data indicate that this transport mechanism could easily cope with both physiological (∼2 μg/mL) 51 and potentially therapeutic concentrations of PRG4 in plasma (in rats, plasma levels of rhPRG4 decayed from ∼200 μg/mL down to ∼20 μg/mL within 40 min after its i.v. injection at 3 mg/kg).…”
Section: Discussionmentioning
confidence: 79%
“…Elevated cartilage degrading enzymes including MMP-1, MMP-3, MMP-13, ADMATS-4, and ADAMTS-5 in the synovial uid of patients with OA are the key enzymes responsible for the progressive degeneration of articular cartilage through degradation of collagen and ECM component [26,27]. Hence, the inhibition of MMPs expression and activation seems to be an attractive therapeutic strategy to prevent and attenuate the progressive degeneration of articular cartilage for maintaining the mechanical function of synovial joints [26].…”
Section: Discussionmentioning
confidence: 99%